ASSOCIATION OF SKINKS WITH CRABS IN THE MANGROVE ECOSYSTEM OF TABONGO VILLAGE, DULUPI SUB-DISTRICT, BOALEMO DISTRICT - Mustapa, Vinarti; K. Baderan, Dewi Wahyuni; Hamidun, Marini Susanti; Katili, Abubakar Sidik; Lamangantjo, Chairunnisah J; Aydalina, Regina Valentine (Indonesian Journal of Chemistry and Environment, 2024)
Mangroves are plants that grow along the coast and have supporting roots. Mangrove ecosystems in addition to protecting the coast from waves and wind are also suitable areas for marine fauna life. One of the fauna found in mangrove ecosystems is the spadefish. Skinks often shelter near the bodies of crabs in order to make it easier for the fish to find food and stay protected from predators. The attachment relationship between these two species growing in the same environment is called association. This study aims to determine the association of silverfish with crabs in the mangrove ecosystem of Tabongo Village, Dulupi District, Boalemo Regency. The study showed that there were 2 species of silverfish and 3 species of crabs, namely Periopthalmus argentilineatus, Periopthalmus malaccensis, Scylla paramamosain, Uca perplexa, and Uca sp. There are 2 types of associations, namely positive associations and negative associations. Positive association with the highest value was found in the pair Periopthalmus argentilineatus with Uca perplexa with a value of 0.37. While the negative association with the lowest value is found in the pair Peripthalmus malaccensis with Uca.